2022
DOI: 10.1111/jfbc.14383
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of glucose gastro‐intestinal enzymes and antioxidant activity of hydrolyzed collagen peptides from different species

Abstract: The growing value of industrial collagen by‐products has given rise to interest in extracting them from different species of animals. Intrinsic protein structure variation of collagen sources and its hydrolysis can bring about different bioactivities. This study aimed to characterize and evaluate the differences in vitro biological potential of commercial bovine (BH), fish (FH), and porcine hydrolysates (PH) regarding their antioxidant and hypoglycemic activities. All samples showed percentages above 90% of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…Consistent with our results, Baskaran et al demonstrated that collagen peptides from Taiwan tilapia skin could increase the cell proportion in the G1 and S phases in different lung cells [37]. Furthermore, the DNA protective effects of collagen peptides derived from different species including fish have been investigated by several research teams [30,38].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our results, Baskaran et al demonstrated that collagen peptides from Taiwan tilapia skin could increase the cell proportion in the G1 and S phases in different lung cells [37]. Furthermore, the DNA protective effects of collagen peptides derived from different species including fish have been investigated by several research teams [30,38].…”
Section: Discussionsupporting
confidence: 89%
“…Multiple studies demonstrated possible cellular mechanisms of the bene cial effects of collagen peptides on alleviating pain and improving joint condition in knee osteoarthritis. These mechanisms include the anti-in ammatory and antioxidant capacities of collagen peptides, and its ability to stimulate collagen synthesis and promote bone formation [22][23][24]. In vitro and in vivo studies showed a reduction of pro-in ammatory cytokines, including IL-1β, IL-6, and TNF-α after collagen peptide administration [22][25] [22].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies showed a reduction of pro-in ammatory cytokines, including IL-1β, IL-6, and TNF-α after collagen peptide administration [22][25] [22]. Collagen peptide also displays antioxidant activities measured by oxygen radical absorbance capacity and radical scavenging assay [24]. Furthermore, evidence has shown that orally administered collagen hydrolysate stimulates a signi cant increase in type II collagen synthesis by chondrocytes [26].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies showed a reduction of pro-inflammatory cytokines, including IL-1β, IL-6, and TNF-α after collagen peptide administration [ 22 , 25 ]. Collagen peptide also displays antioxidant activities measured by oxygen radical absorbance capacity and radical scavenging assay [ 24 ]. Furthermore, evidence has shown that orally administered collagen hydrolysate stimulates a significant increase in type II collagen synthesis by chondrocytes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%